Celebrating Kate: The criminal-celebrity of Sydney underworld figure, Kate Leigh - Straw, Leigh S. L. (2015)
Combining historical study with cultural criminology, this paper analyses the criminal-celebrity of Sydney underworld figure Kate Leigh. It seeks to demonstrate how the three main factors of public resonance—crime type, context and image—created the celebrated criminality of Leigh. Without public resonance, Leigh would have simply remained another criminal within society. An important element of Leigh’s celebrated criminality was her ability to manage a public image that was accepted within the impoverished, working-class communities of eastern Sydney. Leigh became a criminal icon through an entrepreneurial style based on the anti-authoritarian and egalitarian values of working-class life in eastern Sydney. Criminal-celebrity theory provides a framework for understanding the factors enabling the celebration of criminals in society. It also informs historians about the ways in which criminals can manipulate their public image in an effort to legitimise their activities and gain acceptance in the community